Model Edukasi Literasi Keuangan Digital Berbasis Santri Link dalam Mengurangi Perilaku Konsumtif Santri di Pondok Pesantren Mathla’ul Anwar Pontianak - Mubaraq, Abd; Habib Ahmad Alhawari; Ahmad Mubarok; Muhammad Naufal Rizky Ramadhan (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2025)
This study aims to analyze the use of the Santri Link application as a digital financial education tool to reduce consumptive behavior among students at Mathla’ul Anwar Islamic Boarding School, Pontianak. The research employed a quantitative descriptive method, collecting data through observation and questionnaires distributed to 50 respondents. The Likert scale was used to measure students’ agreement levels toward statements regarding their spending behavior and the influence of Santri Link. The findings indicate that the use of the Santri Link application has not increased students’ consumptive behavior. On the contrary, it has encouraged them to manage their spending more wisely, save money, and reduce impulsive buying tendencies. The results also reveal that Santri Link contributes to improving students’ financial literacy and understanding of Islamic financial principles, such as moderation (al-iqtishād) and avoidance of extravagance (isrāf). Overall, the application supports the development of a rational, ethical, and digitally literate financial culture in Islamic boarding schools.